(untitled) (IJM: Journal of Multidisiplinary, 2024)
Students' difficulties in completing tasks assigned by teachers can be an indication of the learning challenges they experience. In a study involving fifth-grade students, it is observed that the average mathematics scores are still below the minimum mastery requirement (KKM). The research method employed combines literature review with a qualitative approach. The findings indicate that learning mathematics can pose challenges for students, particularly in terms of the speed of comprehension and material processing. These difficulties may be related to the complexity of the subject matter or instructional approaches that are not aligned with students' needs. In addressing the mathematics learning difficulties faced by students, it is necessary to implement a more appropriate and diverse approach in the teaching process. A suitable approach will enable teachers to be more sensitive to the individual needs of each student, thereby adjusting teaching methods according to each student's learning style. Furthermore, diverse approaches can help create a more engaging and interactive learning environment, leading to increased student involvement in the learning process.